Literasi Keuangan Terhadap Perilaku Menabung Gen Z, Dengan Moderasi Pengaruh Sosial - Angelyna, Chyntia; Tannia, Tannia (Business Management Journal, 2025)
The saving behavior of Generation Z in Indonesia remains low due to their deep familiarity with technology and social media, which significantly influences their financial habits. Another factor affecting their saving behavior is financial literacy, which remains relatively low in Indonesia. This study explores whether financial literacy significantly influences the saving behavior of Generation Z in Indonesia and whether social influence acts as a moderating variable. This research employs a quantitative approach, with data collection and analysis conducted using SmartPLS 4.0.9.9 software. The testing methods include validity testing, reliability testing, coefficient of determination analysis, and significance testing.The findings indicate that financial literacy has a significant impact on saving behavior. Social influence also significantly affects saving behavior by providing information on saving strategies and techniques relevant to Generation Z. However, social influence does not moderate the relationship between financial literacy and saving behavior, as its effect is limited. This study serves as a valuable reference for policymakers to assess financial literacy and enhance saving behavior in society. One limitation of this research is the small number of respondents, which may affect the strength of the relationships between variables. Future research is recommended to increase the sample size and explore additional variables that may influence saving behavior.